Hybrid CAD/E platform supporting exploratory architectural design. (February 2015) - Zboinska, Malgorzata A.
Abstract: Although computers prove useful in aiding human creativity, there is still shortage of adequate software for early-stage explorations in the design disciplines. One of such under-supported disciplines is architectural design. In response to this lack of proper software, architects adopted tools from other industries with a large level of success. However, despite the fact that several types of such tools have now been employed in conceptual architectural design, their application indicates that they are seldom used altogether. This paper presents a hybrid software platform, bringing these various CAD and CAE tools into one design toolkit. Each platform tool introduces a different possibility of designing, and supports computation-based activities, human intuitive ones, or a mixture of both. The platform user can freely switch between various working styles: algorithmic on the one hand, and fuzzy on the other. Moreover, the designer can perform tasks impossible to execute in traditional design, such as quick generation, exploration and evaluation of large design spaces, containing geometrically-complex solutions. The testing of the hybrid platform in a design experiment indicates its ability to support meaningful early-stage explorations and to yield a highly creative design. One of the aims of investigating a CAD/E platform based on the existing software is to lay the foundations for the development of a future CAD/E system for early-stage architectural design — a tool which is currently missing in the architectural practice. By revealing the potentials of the ready-made software, and by pointing out the technical challenges associated with its integration, we wish to suggest a possible direction for future studies, so that solutions developed by academia have higher chances of being noticed and more widely implemented in praxis. Graphical abstract: Highlights: Hybrid CAD/E platform for early-stage exploratory architectural design is proposed. Platform supports human intuition-based and computation-based workflows. An experiment indicates the potential of the platform to yield creative designs. Technical aspects of CAD/E tool interoperability are presented. Features of platform-inspired future architectural software are pointed out.